GENETIC DIVERSITY OF CITRUS GERMPLASM IN PAKISTAN BASED ON RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) MARKERS - K. Shahzadi; S. Naz; S. Ilyas (Journal of Animal and Plant Sciences, 2016)
Citrus has a long history of cultivation in the world and is considered as an economically important fruit crop. In south Asia together with Pakistan many varieties are widely grown for exports as well as domestic use. Therefore considering the importance, current study is aimed to identify and evaluate the genetic diversity of 17 Pakistani Citrus cultivars with 14 RAPD (Random amplified polymorphic DNA) markers. From the screening of 30 primers, a total of fourteen decamer primers were chosen that produced 8.35±0.41 bands per primer on average with 96 polymorphic bands of 117 total bands. The phylogenetic relationship was assessed by using Jaccard’s similarity coefficient. The phylogenetic tree separated 17 Citrus genotypes into 3 main groups using analysis of Unweighed Pair Group Method with Arithmetic Mean. The similarity coefficient detected across all the genotypes was 0.66 with two cultivars of mandarin (Fallglo and Murcott) and grapefruit (Chakotra and Ruby red) showing the highest similarity value of 0.92. High genetic distance illustrated difference in origin of 17 Citrus cultivars. The current study revealed the successful utilization of genetic marker i.e. RAPD to analyze the phylogenetic relationship and genetic diversity among the citrus varieties hence can be recommended as well to be used in Citrus breeding programs.
Keywords: Citrus genotypes; Genetic characterization; Polymerase chain reaction; Phylogenetic relationship; RAPD